GATEKEEPER Platform: Secure Processing Environment for European Health Data Space - Eugenio Gaeta; Muhammad Salman Haleem; Laura Lopez-Perez; Mirko Manea; Maria Fernanda Cabrera Umpierrez; Maria Teresa Arredondo Waldmeyer; Leandro Pecchia; Giuseppe Fico (IEEE Access)
The European Health Data Space (EHDS) is a significant initiative within the European Union aimed at improving healthcare through better use of health data and collaboration. This involves sharing and utilization of health data in a secure and interoperable manner across EU member states. With the advent of modern technology, different types of health data are being acquired ranging from traditional electronic health records to real-time wearable signals for improved healthcare delivery and management. However, there are certain challenges associated with compliance to EHDS, such as secure continuous integration (CI) and continuous delivery (CD), scalability and adaptability towards new technologies and applications, tolerance against IoT cyber-attacks, requirement of advanced data storage methods, processing power, interoperability solutions for data analysis and connectivity. In order to address these, a flagship project of the European Commission, GATEKEEPER, represents a pioneering effort designed to transform healthcare delivery through the utilization of sophisticated digital technologies. The architecture of the GATEKEEPER platform has been meticulously crafted, in compliance with the EHDS, to integrate a multitude of data sources, deploying advanced analytical tools to enable the development of novel solutions for the effective prediction, detection, and management of chronic health conditions. GATEKEEPER addresses the aforementioned challenges by integrating collaborative tools for data management and consistency, machine learning modelling and management tool, activity feeds and issue tracking tools with developers authentication, CI/CD tools allowing, among others scalability in multiple formats, tools for assessing security, vulnerability and dependency for third party packages.